Comparing Detector Magnetic Systems for the Future Circular Hadron-Hadron Collider - Klyukhin, Vyacheslav; Ball, Austin; Berriaud, Christophe Paul; Curé, Benoit; Dudarev , Alexey; Gaddi , Andrea; Gerwig, Hubert; Hervé, Alain; Mentink, Matthias; Riegler, Werner; Wagner, Udo; Kate, Herman Ten (Science and Technology - Recent Updates and Future Prospects Vol. 1, 2024)
This work describes a detailed study of two possible options for the magnetic system of a Future Circular hadron-hadron Collider detector. The conceptual design study of a Future Circular hadron-hadron Collider (FCC-hh) to be constructed at CERN with a center-of-mass energy of the order of 100 TeV requires superconducting magnetic systems with a central magnetic flux density of an order of 4 T for the experimental detectors. The developed concept of the FCC-hh detector involves the use of an iron-free magnetic system consisting of three superconducting solenoids: the main coil of 10.9 m inner diameter and 18.954 m length with a total current of 69.6 MA-turns that give a central magnetic flux density of 4 T, and two superconducting forward coils of 5.6 m inner diameter and 3.3997 m length with a total current of 12.6 MA-turns each that give a central magnetic flux density of 3.2 T in each coil. A superconducting magnet with a minimal steel yoke is proposed as an alternative to the baseline iron-free design. This design includes the same three coils enclosed in the 22,240-ton steel flux-return yoke. In this study, both magnetic system options for the FCC-hh detector are modeled with Cobham’s program TOSCA. All the main characteristics of both designs are compared and discussed.